Mobile video streaming and sharing in social network using cloud by the utilization of wireless link capacity (International Journal of Engineering and Computer Science, 2014)
As and when the mobile users are increasing in day by day the demands of video traffic over mobile networks keep on rising, so the wireless link capacity cannot satisfying the demands of mobile user due to the variation in the link status and many disruptions, it causes long time buffering to mobile user. To overcome from this a framework is proposed for the efficient utilization of wireless link capacity by the combination of Adaptive mobile video streaming [AMoV] and Efficient social video sharing [ESoV] techniques using cloud. In AMoV, there is a combination of adaptability and scalability features. So that it provides efficient utilization of bandwidth. Likewise ESoV provides efficient social video sharing by use of same combination of features. So that user experiences continuous flow of video streaming by avoid of buffering.